Playing work, or gamification as stultification. Issue 9 (2nd September 2018) - Bateman, Chris
ABSTRACT: The contrast between work and play as activities collapses if play is seen, following anthropologist Thomas Malaby, as a disposition towards the indeterminate. Once play is positioned as a state of mind, activities that constitute work need not be disjunct from playful behavior. Yet for most workers, work is rarely if ever playful, and attempts to import play behavior into the workplace ('gamification') do not result in greater playfulness. Part of this problem results from specific aesthetic values for games having dominated both work and play. As Roger Caillois warned half a century ago, sport-like values have increasingly saturated the culture of the overdeveloped world. Meanwhile, gamification processes have only been able to export task-focussed reward structures from the domain of play – practices that descend from Dungeons & Dragons, but that have been denuded of their playful qualities. In parallel to the gamification of work has been the gamification of games, namely an increasing emphasis on tasks to structure video game play (e.g., achievements), and thus make them more compelling yet less playful. In so much as this entails forcing particular patterns of understanding onto both players and workers, this makes gamification a parallel to Jacques Rancière's stultification in education: a binding of wills instead of an emancipation. If we want a world where work could be more playful, we must begin by breaking the cultural dominance of sport-like and task-like aesthetics of play, and endeavour to overcome the underlying fears that prevent work from being played.